Exploring the Association Between Psychological Distress and Cannabis Edible Use Among U.S. Adults: A Short Review - Ul Haq, Zeeshan; Hasan, Md Rakibul (LIAQUAT MEDICAL RESEARCH JOURNAL, 2025)
Cannabis edibles have become increasingly popular in the United States (U.S), however, limited research has explored their relationship with mental health. This study examined whether adults experiencing past-month psychological distress were more likely to use cannabis edibles compared with those without distress. Data were drawn from the 2023 National Survey on Drug Use and Health (NSDUH). Adults aged ? 18 years were included. Past-month cannabis edible use (IRMJMONEAT) was the dependent variable, and past-month psychological distress (SPDPSTMON) was the primary predictor variable. Weighted prevalence estimates and survey-weighted logistic regression models were applied, adjusting for relevant sociodemographic and behavioral factors. The Weighted prevalence of edible use was 5.6% (95% CI 5.2–5.9) among adults without distress and 13.5% (95% CI 12–15) among those with distress. In the adjusted regression models, psychological distress was significantly associated with edible use (AOR = 1.44, 95% CI 1.21–1.71, p < 0.001). In conclusion the psychological distress was independently associated with hight cannabis edible use among U.S. adults. These findings underscore the importance of integrating mental-health screening and harm-reduction strategies into cannabis prevention and treatment frameworks.